The Effectiveness of Utilizing the Fabric Order Information System at PT Ateja Tritunggal Using the PIECES Method - Kurniawan, Kurniawan (CoreID Journal, 2024)
The development of information technology has brought significant impacts to the business world, including the manufacturing industry. One important aspect in the textile industry is the production of fabric orders. PT Ateja Tritunggal also faces challenges in managing the fabric order information system. The PIECES (Performance, Information, Economy, Control, Efficiency, and Service) method framework is a framework used for classifying problems, opportunities, and directions within the scope of system analysis and design definitions. This study aims to analyze the effectiveness of fabric order production at PT Ateja Tritunggal using the PIECES method. This research uses quantitative methods and data collection techniques through a survey using questionnaires conducted using Google Forms media to all personnel in the PPIC (Planning Product Inventory Control) department at PT Ateja Tritunggal. The test results showed that the information system running at PT Ateja Tritunggal falls into the good category, but there is a need for improvement so that all business processes can run more effectively and properly.